2019
DOI: 10.1080/02626667.2019.1661415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the influence of river flow confluences on the open channel stage–discharge relationship

Abstract: An accurate assessment of the stage-discharge relationship in open channel flows is necessary and important to the design and management of hydraulic structures and engineering in practical hydrosystems such as rivers and streams. While the flow structures and patterns at open channel junctions are interesting and have been widely studied in the literature, this paper focuses further on the effect of flow junctions on stage-discharge relationship at mountain river confluences. In this study, both the flume and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…9a, b that the velocity profiles in line 1 are in the flow deflection zone with lower velocity values in comparison with lines 2-4. This trend in velocity profiles is similar to the results of Wang et al (2019). It should be noted that due to the mixing of the flow and bed topography caused by bedload (Fig.…”
Section: Time Average Velocity Profilessupporting
confidence: 87%
See 1 more Smart Citation
“…9a, b that the velocity profiles in line 1 are in the flow deflection zone with lower velocity values in comparison with lines 2-4. This trend in velocity profiles is similar to the results of Wang et al (2019). It should be noted that due to the mixing of the flow and bed topography caused by bedload (Fig.…”
Section: Time Average Velocity Profilessupporting
confidence: 87%
“…Recently, Wang et al (2019) evaluated the stage-discharge relationship at a channel confluence and a scaled model of a river confluence in China. They showed that the water level at the main channel increased due to the tributary channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the area of the stagnation zone at the upstream corner of the tributary channel with the main channel increases with decreasing the W*. It is caused by the effect of the higher downward velocity from the narrower tributary channel, which causes a higher upstream water level or backwater effect [21]. It is similar to increases in the tributary channel discharge in studies such as ref.…”
Section: Longitudinal Velocity Distribution and Flow Patternsmentioning
confidence: 57%
“…It is observed that the maximum value of the V velocity takes place at the downstream corner of the tributary channel with the main channel and its value and gradient increases as the tributary width decreases.In addition, the area of the stagnation zone at the upstream corner of the tributary channel with the main channel increases with decreasing the W*. It is caused by the effect of the higher downward velocity from the narrower tributary channel, which causes a higher upstream water level or backwater effect[21]. It is similar to increases in the tributary channel discharge in studies such as ref [2].…”
mentioning
confidence: 69%
“…Understanding the fluvial process in the mountain river confluence is beneficial for natural hazard assessments (Badoux et al, 2014) and river restoration (Guillén‐Ludeña et al, 2016). Different from a lower‐gradient river confluence, a mountain river confluence is commonly identified with the low discharge ratio of the tributary to the main channel, sediment source largely fed by the tributary and discharge fed by the main channel, a wide range of sediment size leading to bed armouring, and large bed slope difference between the tributary and main channel (Canelas et al, 2020; Guillén‐Ludeña et al, 2016; Leite Ribeiro et al, 2012; Wang et al, 2019). Due to the marked hydro‐morphological features, mountain river confluences show distinct behaviours compared with plain river confluences.…”
Section: Introductionmentioning
confidence: 99%